Farmers’ Satisfaction Level in Conducting a Profit-Sharing System (Tesang) of Beef Cattle Business in Bone, South Sulawesi - Firdayanti, Firdayanti; Baba, Syahdar; Asnawi, Aslina (Hasanuddin Journal of Animal Science (HAJAS), 2024)
Beef cattle farming in some areas is carried out by raising their own cattle and some raise cattle with a profit-sharing system or in Bugis Macassar culture known as tesang/teseng. Tesang is a profit-sharing pattern between the capital provider and the farmer. This study aims to determine the level of satisfaction of capital owners (ma'tesang) and breeders (pattesang) and capital owners (ma’tesang) in conducting a profit-sharing system and to determine the factors that affect the satisfaction of breeders (pattesang) in conducting a profit-sharing system. This study used a questionnaire to collect data in the form of the level of importance (expectations) and the level of performance (reality) experienced by each breeder measured based on the dimensions and indicators of measuring the level of satisfaction. The data were analyzed using the IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index) methods and multiple linear regression using SPSS. The results showed that based on IPA and CSI analysis the results obtained were the level of satisfaction of the capital owner was 85.57% and the breeder was 80.21%. So that based on the predetermined criteria index, the level of satisfaction of capital owners and breeders is on a scale of Very Satisfied with the profit-sharing system. Based on the results of this study, it can be concluded that overall farmers and capital owners are very satisfied in conducting tesang. Keywords: Capital Owner; Farmer; Satisfaction Level; Tesang.